2009
DOI: 10.1303/aez.2009.267
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of egg-hatching rate, survival rate and development time of the immature stage between B- and Q-biotypes of Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) on various agricultural crops

Abstract: Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) B-and Q-biotypes are exotic insects in Japan and are consequently regarded as insect pests in agricultural fields. Using B-and Q-biotypes, we investigated the hatching rate, survival rate during the larval stage and the total development period from egg to adult. Whiteflies were allowed to lay eggs on several host plants: cabbage, Brassica oleracea var. capitata; cucumber, Cucumis sativus L.; tomato, Solanum lycopersicum L.; eggplant, Solanum melongena L.; be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 29 publications
10
81
3
1
Order By: Relevance
“…By contrast, our host-plant experiment confirmed previous research finding that MEAM1 was dominant over MED on most, but not all, plant species ( Fig. 4; Iida et al 2009, Tsueda and Tsuchida 2011, Liu et al 2013b. Specifically, our results agree with work (Tsueda and Tsuchida 2011) that found MEAM1 could not develop on pepper but did better than MED on tomato, cabbage, and cucumber.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, our host-plant experiment confirmed previous research finding that MEAM1 was dominant over MED on most, but not all, plant species ( Fig. 4; Iida et al 2009, Tsueda and Tsuchida 2011, Liu et al 2013b. Specifically, our results agree with work (Tsueda and Tsuchida 2011) that found MEAM1 could not develop on pepper but did better than MED on tomato, cabbage, and cucumber.…”
Section: Discussionsupporting
confidence: 91%
“…Second, both mating and oviposition are likely to be initiated in B. tabaci when pairs are experimentally placed with host plant leaves (e.g., Sun et al 2011). Third, these two biotypes show better adult and offspring performance on different crop species (Muñiz 2000;Iida et al 2009). Moreover, in the Israel population, the Q biotype has higher pesticide resistance than the B biotype.…”
Section: White Butterflies (Leptidea)mentioning
confidence: 98%
“…From the results of a spatially explicit model, Crowder et al (2011) showed that regional coexistence of these two biotypes is possible when large differences in performance exist within the region. It is unclear whether difference in performance is higher in Israel than in China and Australia, but variations in crop species and cultivars (Iida et al 2009) as well as in pesticide management (Crowder et al 2010b) can cause difference in performance. Thus, the whitefly system is appropriate for identifying those factors that affect the regional coexistence of a focal species and a highly interfering species, a necessary condition for the maintenance of host selection differences.…”
Section: White Butterflies (Leptidea)mentioning
confidence: 99%
“…This acts as a source of water transport from the tissues to the eggs (Paulson and Beardsley, 1985;. This mortality may be attributed to egg hatch failure due to certain reasons like problem of improper solute uptake through egg stalk (Iida, 2009;Kakimoto et al, 2007), and egg might have taken up certain chemicals through stalk depending upon host plant that might have spoiled the eggs (Iida, 2009).…”
Section: Age Specific Survival Expectation and Mortalitymentioning
confidence: 99%